I'm struggling to prove the following statement, which makes intuitive sense:

Let $f: \mathbb{R} \to \mathbb{R}$ be differentiable. Suppose $\forall x \in \mathbb{R} \quad 0 \le f'(x) \le f(x)\,$. If $f$ vanishes at some point, show that $f$ is identically zero.

This is exercise 6 in section 6.7, in Elementary Classical Analysis by Mardsen & Hofmann.

I've managed to do the following:

Let $\omega \in \mathbb{R}$ be the point such that $f(\omega) = 0$ (which exists by hypothesis). Let $x < \omega$. By Cauchy's Mean Value Theorem,

$$ \exists \xi \in (x, \omega)\colon\quad 0 \le f(x) =f(x) - f(\omega) = f'(\xi)(x - \omega)\,. $$

By hypothesis, we have that $f'(\xi) \ge 0$. On the other hand, $x - \omega < 0$. Thus, $f'(\xi)(x - \omega) \le 0$. By the above proposition, though, $ f'(\xi)(x - \omega) \ge 0\,$. Therefore, $f'(\xi) = 0$ which implies $f(x) = 0$.

With this we have proven that $\forall x \in \mathbb{R}\quad x \le \omega \rightarrow f(x) = 0\,$.

But for $x > \omega$, I haven't been able to prove much. I've got so far:

Let $x > \omega$. By Cauchy's Mean Value Theorem,

$$ \exists \xi_1 \in (\omega, x)\colon\quad 0 \le f(x) = f(x) - f(\omega) = f'(\xi_1)(x - \omega) \le f(\xi_1)(x - \omega)\,. $$

If we apply this reasoning recursively on $f(\xi_1)$, we get a succession $(\xi_i)_{i\in\mathbb{N}} \subseteq (\omega, x)$ such that $\forall i \in \mathbb{N}\quad \xi_{i+1} \in (\omega, \xi_i)$ and

$$ \forall n \in \mathbb{N}\quad f(x) \le f(\xi_n) \prod_{i = 0}^{n - 1} (\xi_i - \omega) $$

where $\xi_0 = x$.

Is there a hint?


2 Answers 2


$(e^{-x}f(x))'=e^{-x}(f'(x)-f(x)) \leq 0$ so $e^{-x}f(x)$ is decreasing. If $f(x_o)=0$ then $e^{-x}f(x)$ is non-negative and $\leq e^{-x_0}f(x_0) =0$ for $x>x_0$ so $f(x)=0$ for $x \geq x_0$. For $x \leq x_0$ you already have a proof.


The idea is to see that if $f \neq 0$, then there exists $y>\omega$ such taht $\forall x \geq y, f(x)>0$. For such an $x$ you have $\dfrac{f'(x)}{f(x)}\leq 1$. You can integrate and this gives $f(x) \leq e^x$, thus giving an hint to introduce the function $g(x)\doteq f(x)e^{-x}$. You can work from that point.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.